2019
DOI: 10.14202/vetworld.2019.1150-1153
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasites of dogs (Canis familiaris) in Maiduguri, Borno State, Northeastern Nigeria: Risk factors and zoonotic implications for human health

Abstract: Aim: This study was designed to investigate the prevalence, associated risk factors, and zoonotic implications of gastrointestinal parasites of dogs in Maiduguri, Borno State, Northeastern Nigeria. Materials and Methods: A total of 200 rectal fecal samples were collected from dogs in Maiduguri for coprological examination using the saturated sodium chloride floatation technique. Detection of eggs or oocyst was done on the basis of keys of identification of parasites based on the morphology and size of eggs or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
1
2
1
1
Order By: Relevance
“…The high prevalence of Ancylostoma spp., Cryptosporidium spp., and Toxocara spp. detected in the feces of sampled dogs recapitulates previous reports in Nigeria (Ayinmode et al, 2016;Ezema et al, 2019;Kamani et al, 2021) and outside Nigeria (Abere et al, 2013;Ngui et al, 2014;Torres-Chablé et al, 2015). The prevalence rates of 33.24%, 36.45%, and 41.67% for Ancylostoma spp., Cryptosporidium spp., and Toxocara spp., respectively, have been reported among dogs in Nigeria (Ugbomoiko et al, 2008;Idika et al, 2017;Eze et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…The high prevalence of Ancylostoma spp., Cryptosporidium spp., and Toxocara spp. detected in the feces of sampled dogs recapitulates previous reports in Nigeria (Ayinmode et al, 2016;Ezema et al, 2019;Kamani et al, 2021) and outside Nigeria (Abere et al, 2013;Ngui et al, 2014;Torres-Chablé et al, 2015). The prevalence rates of 33.24%, 36.45%, and 41.67% for Ancylostoma spp., Cryptosporidium spp., and Toxocara spp., respectively, have been reported among dogs in Nigeria (Ugbomoiko et al, 2008;Idika et al, 2017;Eze et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the overall prevalence of gastrointestinal nematodes is 36.5%. This is higher than 22.4% reported by Esonu et al, (2019) in Zaria and 31.5% reported by Ezema et al, (2019) in Maiduguri. The higher prevalence might be due to the cohabitation and mingling of many non-infected dogs with infected dogs which enhances cross transmission resulting from continuous environmental contamination with eggs from infected feaces.…”
Section: Discussioncontrasting
confidence: 61%
“…A lower prevalence ranging from 0.1% ( n = 3099) [ 28 ] to 0.8% ( n = 2193) [ 29 ] was reported in dogs in Brazil, whereas a higher prevalence of up to 75% ( n = 160) was reported in Nigeria [ 30 ]. Some recent studies have reported a prevalence of 4.5% ( n = 200) in Nigeria [ 31 ], 1.9% ( n = 263) in Spain [ 32 ], 16.5% ( n = 103) in stray dogs in Mexico [ 33 ], 11.8% ( n = 152) in Pakistan [ 34 ], 6% ( n = 63) in Portugal [ 35 ], and 3.1% ( n = 360) in stray dogs in Sudan [ 36 ]. The difference in the prevalence of D. caninum infection in dogs in different countries could be attributed to differences in the health care system and management of dogs, geographical areas, environmental sanitation, and the level of flea infestation in dogs [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%